Occurence of Cooperia curticei (Giles 1892), (Nematoda: Trichostrongylidae), parasite of cattle in cantagalo, state of Rio de Janeiro - Duarte, Maria José de Faria; Gomes, Plínio Antônio Costa; Tristão, Mauro Sérgio Guimarães (Pesquisa Agropecuaria Brasileira, 2014)
Cooperia curticei (Giles, 1892) (Nematoda: Trichostrongylidae) is reported for the first time, parasitizing the small intestine of cattle in the State of Rio de Janeiro, Brazil. The animals, came from Cantagalo.